A force-control scheme for biped robots to walk over uneven terrain including partial footholds. (20th January 2020) - Sygulla, Felix; Rixen, Daniel
The robustness of biped walking in unknown and uneven terrains is still a major challenge in research. Traversing such environments is usually solved through vision-based reasoning on footholds and feedback loops—such as ground force control. Uncertain terrains are still traversed slowly to keep inaccuracies in the perceived environment model low. In this article, we present a ground force-control scheme that allows for fast traversal of uneven terrain—including unplanned partial footholds—without using vision-based data. The approach is composed of an early-contact method, direct force control with an adaptive contact model, and a strategy to adapt the center of mass height based on contact force data. The proposed method enables the humanoid robot Lola to walk over a complex uneven terrain with 6 cm variation in ground height at a walking speed of 0.5 m/s. We consider our work a general improvement on the robustness to terrain uncertainties caused by inaccurate or even lacking information on the environment.